COVID-19 pandemic: two year experience and response of a teaching hospital in Malaysia and the effect on postgraduate orthopaedic training - Kow, Ren Yi; Khalid, Kamarul Ariffin; Zakaria@Mohamad, Zamzuri; Awang, Mohamed Saufi (Malaysian Orthopaedic Association, 2022)
As the number of COVID-19-related infections and deaths increased exponentially in the during 2020, few countries were equipped to manage and curb this novel coronavirus. Initially there was no proven cure or vaccine to this novel virus (SARS-Cov-2), leaving the authorities with no choice but to impose quarantines at the short-term expense of their economies. As we gain more knowledge on this novel virus, the tried-and-tested method of selective testing of the symptomatic patients, used successfully in almost all infectious respiratory diseases, has been replaced with trace-and-test method, as most of the infected patients remained asymptomatic. In early 2021, the availability of vaccines provided a shed of light out from this pandemic. Nevertheless, we faced an enormous task in juggling between vaccination of the population, managing patients with COVID-19 infection as well as non-COVID-19 patients. Here, we share our experience and response in managing this healthcare crisis across a two-year period during the pandemic and we hope other centres can learn from what we went through and help them derive a protocol to navigate through a future pandemic.